Analisis Pengembangan Ekonomi Di Kota Medan - Ripaldo Hasibuan, Muhammad Rezki; Harahap, Rahmat Daim (Jurnal Manajemen Akuntansi (JUMSI), 2022)
Economic development or economic growth is a continuous change in the economic conditions of a community group towards a better state. The purpose of this research is to find out how the economic development in Medan city is based on the results of the internship analysis that the researchers did. The research method used in this study uses qualitative methods. To improve regional development, especially in developing areas, the regional government seeks to improve the welfare of the community by exploring and developing the potentials that exist in the region through Economic Development.